Exploration of Sustainable Development Strategies for Budai Opera in the Eastern Fujian Region - Bao, Shuhui; Dang, Weibo (Journal of Ecohumanism, 2024)
This study explores sustainable development strategies for Budai Opera in the Eastern Fujian region, aiming to preserve and promote this traditional art form amidst modern challenges. Through a mixed-method approach, including qualitative interviews, quantitative surveys, and observational data, diverse dimensions of Budai Opera sustainability are examined. Results reveal a diverse demographic profile of stakeholders, varying levels of awareness and interest in Budai Opera, and preferences for cultural events. Economic viability, environmental impact, community engagement, policy support, audience preferences, and technological innovations are also explored. Key findings emphasize the importance of holistic approaches that balance economic, cultural, environmental, and social considerations in promoting Budai Opera sustainability. Addressing challenges such as declining audiences, economic pressures, environmental impacts, and policy constraints, while capitalizing on opportunities for diversification, innovation, community engagement, and advocacy, are essential for sustaining Budai Opera as a cherished cultural heritage in the Eastern Fujian region.